PENGEMBANGAN PERANGKAT PEMBELAJARAN MATERI SEGIEMPAT DAN SEGITIGA KELAS VII MELALUI MODEL PROBLEM BASED LEARNING - Husna, Miftahul; Kartini, Kartini; Murni, Atma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The background of this research is the restrict of mathematics learning instruments as supporting learning referring to 2013 Curriculum. This research aimed to develop mathematics learning device that are Lesson Plan (LP) and Students Worksheet (SW) based curriculum 2013 in subject quadrilateral and triangle of seventh grade through problem based learning model. This research and development use 4-D development model by Thiagarajan which includes: (1) define, (2) design, (3) develop, and (4) disseminate. At the stage of define, the researcher conducted a needs analysis as first-end analysis, analysis characteristic of students, concept analysis, assignment analysis and learning aim specification. Furthermore gather the necessary materials to design LP and SW. Learning device that had been developed then validated by three validators and revised based on the input from validators.The valid learning device then tested in two stages, the small group trial with subjects are 10 students of class VII6 SMP Negeri 8 Pekanbaru and large group trial with subjects are 34 students of class VII5 SMP Negeri 8 Pekanbaru. Based on the data analysis and discussion can be concluded that the LP and SW in quadrilateral and triangle subject of seventh grade through problem based learning model are valid with an average value for the LP is 3.53 and the average value for SW is 3.45, and SW is practical to use by learners class VII.Keywords: Mathematics Learning Instrument, Problem Based Learning Model, Quadrilateral and Triangle.